Women with HIV – a case study in a rehabilitation centre in Malaysia / Badariah Mohd Saad, Nooriha Abdullah and Geetha Subramaniam - Mohd Saad, Badariah; Abdullah, Nooriha; Subramaniam, Geetha (UiTM Press, 2018)
The main aim of this study is to examine the awareness and knowledge, lifestyle and education on HIV/AIDS. Utilising a semi-structured questionnaire, interviews were conducted among four Malay women who had HIV/AIDS in a Rehabilitation Centre in Selangor, Malaysia. A post-interview analysis of the transcripts was conducted through close reading of the entire transcriptions of the interviews in order to search for underlying themes/variables. The findings show three respondents contracted HIV through random sex and were infected during their early 20s and 30s while one respondent got infected through the husband. While poverty is an issue, awareness is still lacking on modes of transmission of HIV/AIDS. More concerted efforts by the government via education and health policies at primary schools to instil awareness on HIV and its consequences.